2021
DOI: 10.3390/ijerph18094707
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of ‘Just Right’ Physical Behavior in Industrial Work Based on the Goldilocks Work Principle—A Feasibility Study

Abstract: The Goldilocks Work Principle expresses that productive work should be redesigned to comprise physical behaviors of different intensities in a composition promoting workers’ health and fitness. This study is the first to assess the feasibility of redesigning work in an industrial setting according to the Goldilocks Work Principle. We recruited workers (n = 20) from a brewery in Denmark, and we conducted a participatory 16-week intervention including a workshop and two consultations. The workshop aimed to suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Increasing variation in the physical demands could also be meaningful, and could include workers rotating between work tasks, job categories, or departments [ 14 , 18 , 20 ] with higher and lower physical demands and different exposure profiles, e.g., alternating heavy lifting, cashier work, and rest. Recently, a feasibility study has suggested that work can be re-organized and thereby reduce fatigue and pain while also increasing energy [ 59 ], and this could theoretically also work in supermarkets due to the high diversity in work tasks and hence variation in exposure profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing variation in the physical demands could also be meaningful, and could include workers rotating between work tasks, job categories, or departments [ 14 , 18 , 20 ] with higher and lower physical demands and different exposure profiles, e.g., alternating heavy lifting, cashier work, and rest. Recently, a feasibility study has suggested that work can be re-organized and thereby reduce fatigue and pain while also increasing energy [ 59 ], and this could theoretically also work in supermarkets due to the high diversity in work tasks and hence variation in exposure profiles.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the intervention, each operations manager will be provided with a “GoldiCare tool” developed in Microsoft Excel to support a more even distribution of high ADL patients among home care workers. The GoldiCare tool was inspired by a similar Goldilocks Work intervention implemented in Denmark [ 17 ]. The GoldiCare tool was tested in a feasibility study (unpublished), and an adjusted version was adopted for the present intervention.…”
Section: Methods—participants Interventions and Outcomesmentioning
confidence: 99%
“…Moreover, the vision of the Goldilocks Work Principle is that the just right distribution not only prevents poor health, but also promotes workers’ health and capacity. While the feasibility of Goldilocks interventions have been investigated in other sectors, such as child care [ 16 ] and manufacturing [ 17 ] no randomized controlled trial has been conducted in home care to date.…”
Section: Introductionmentioning
confidence: 99%
“…The Goldilocks Work Principle proposes that occupational physical activity can be designed to comprise a 'just-right' balance of physical behaviors, including intense periods, alternating with recovery, that can promote workers' health and fitness [15]. In prior research we found that industrial workers stand for a large portion of the workday, have little variation in their physical behaviors, limited time for recovery, and limited time at an intensity which would promote cardiovascular fitness [16]. Accordingly, increasing their time spent sitting (to support recovery), their time being active, and their frequency of alternations between these behaviors could promote their musculoskeletal health [7,15,17].…”
Section: Background and Rationalementioning
confidence: 99%